Synthesis, crystal structure and thermal properties of N′-[(E)-3,5-di-tert-butyl-2-hydroxybenzylidene]-2-hydroxybenzohydrazide ethanol quatersolvate - Mamadou Lo; Bineta Sene; Anastasie Manga; Aissatou Alioune Gaye; Abdoulaye Gassama; Amadou Diop; Arie van der Lee; Sébastien Richeter (Acta Crystallographica Section E: Crystallographic Communications)
In the structure of the title compound, 4C22H28N2O3·C2H6O, molecules composed of an acylhydrazone segment bridging a 3,5-di-tert-butylphenol unit and a 2-hydroxyphenol unit form columnar quartet channels along the a-axis, within which disordered ethanol solvent molecules reside in two inversion-centre-related positions. Intermolecular hydrogen bonds assemble the channels between the columnar molecules through the hosted ethanol molecule, complemented by weaker van der Waals-type interactions. These weak van der Waals interactions also hold the columns together. Additionally, the title compound demonstrated notable thermal stability at temperatures of up to 251°C. The sharp melting point peak observed in the DSC confirmed its crystalline structure.